Description of the male Eufriesea theresiae (Mocsáry, 1908) (Hymenoptera: Apidae: Euglossina), with illustration of the holotype and comments on its geographic distribution, including a new record for the state of Pará, northern Brazil - Nemésio, André (Zootaxa, 2011)
Members of Eufriesea Cockerell, 1908 (Hymenoptera: Apidae: Euglossina) are highly seasonal (Kimsey 1982) and, thus, usually poor represented in entomological collections. Even when active, Eufriesea spp. rarely occur in high densities; Eufriesea violacea (Blanchard, 1840) being one of the few exceptions (e.g., Uehara-Prado & Garófalo 2006). Moreover, males of some species seem to be poorly attracted to the chemicals usually used in orchid-bee inventories (see discussion in Nemésio & Silveira 2004). Thus, many species of Eufriesea are known from few specimens, some of them only from the type series or type specimens.